Real gas model for an electric swashplate refrigeration compressor. (October 2020) - Arqam, Mohammad; Dao, Dzung Viet; Jahangiri, Amir; Mitchell, Mark; Woodfield, Peter
Highlights-(JIJR-D-19-00930): A real-gas, restricted-flow valve model is developed for the swashplate compressor. The model agrees well with experimental data for R134a and R1234yf. In-cylinder heat transfer was found to be of lesser importance. Pressure drop across the discharge valve was found to be of lesser importance. Suction valve flow coefficient has a significant effect on volumetric efficiency. Abstract: A real-gas, restricted-flow valve model is compared with an ideal-gas, ideal-valve model for a 10-cylinder swashplate refrigeration compressor. Real gas properties of R134a are evaluated using the NIST standard reference database. A minor-loss discharge-coefficient approach is used to model the refrigerant flow rate through reed valves while the ideal-valve model requires no pressure difference to open the valve. In contrast with the ideal model, the discharge temperature, refrigerant mass flow rate and volumetric efficiency as a function of rotational speed are predicted well by including real-gas properties and flow restriction on the inlet valve. The ideal-gas model significantly overpredicts the discharge temperature and shows no dependence on rpm. Heat transfer to and from the cylinder wall during compression and expansion is found to have only a small effect on predictions of compressor performance. The valve model for the suction side has the largest influence on compressor performance predictions as a function of rpm.